A Case Report Examining Early Extubation Following Congenital Heart Surgery in a Low Resource Setting - Howes, Catherine (Frontiers in Pediatrics, 2019)
This case report aims to critically analyse the evidence surrounding early extubation in the post-operative phase following complex congenital cardiac surgery. Child A was an eight year old female who had undergone complex congenital cardiac surgery during an international surgical charity mission. On her admission to the paediatric intensive care unit Child A appeared to be in good condition and no major complications had occurred intra-operatively. This was considered alongside the situational pressures of resource limitations and the missions aim to offer surgery to as many children as possible during the available time frame. The decision was made by the team that Child A was a suitable candidate for ‘early extubation’. Some members of the team were uncomfortable with this approach and felt it could lead to poorer outcomes for patients. Current evidence surrounding early extubation both within international surgical mission trips to low-income and mid-income countries and established cardiac centres within high-income countries is examined and discussed alongside the context of resource limitation. Although the process and implications of early extubation following cardiac surgery need further research, on the basis of the evidence currently available clinicians could potentially encourage the use of early extubation within clinical practice for appropriately selected patients through the utilisation of a multidisciplinary approach both within the UK and during international surgical charity missions to low-income and mid-income countries.